Infant mortality and isotopic complexity: New approaches to stress, maternal health, and weaning. Issue 3 (13th March 2015) - Beaumont, Julia; Montgomery, Janet; Buckberry, Jo; Jay, Mandy
ABSTRACT Objectives: Studies of the carbon and nitrogen stable isotope ratios (δ13C and δ15N) of modern tissues with a fast turnover, such as hair and fingernails, have established the relationship between these values in mothers and their infants during breastfeeding and weaning. Using collagen from high‐resolution dentine sections of teeth, which form in the perinatal period we investigate the relationship between diet and physiology in this pivotal stage of life. Materials and Methods: Childhood dentine collagen δ13C and δ15N profiles were produced from horizontal sections of permanent and deciduous teeth following the direction of development. These were from two 19th‐century sites (n = 24) and a small number (n = 5) of prehistoric samples from Great Britain and Ireland. Results: These high‐resolution data exhibit marked differences between those who survived childhood and those who did not, the former varying little and the latter fluctuating widely. Discussion: Breastfeeding and weaning behavior have a significant impact on the morbidity and mortality of infants and the adults they become. In the absence of documentary evidence, archaeological studies of bone collagen of adults and juveniles have been used to infer the prevalence and duration of breastfeeding. These interpretations rely on certain assumptions about the relationship between isotope ratios in the bone collagen of the adult females and the infants who have died. The data from this study suggest a more complex situation than previously proposed and the potential for a new approach to the study of maternal and infant health in past populations. Am J Phys Anthropol 157:441–457, 2015. © 2015 Wiley Periodicals, Inc.